2018
DOI: 10.1021/acs.nanolett.7b03390
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and Contamination-Dependent Electrical Properties of Carbon Nanotubes

Abstract: Two-point probe and Raman spectroscopy have been used to investigate the effects of vacuum annealing and argon bombardment on the conduction characteristics of multiwalled carbon nanotubes (MWCNTs). Surface contamination has a large effect on the two-point probe conductivity measurements which results in inconsistent and nonreproducible contacts. The electric field under the contacts is enhanced which results in overlapping depletion regions when probe separations are small (<4 μm) causing very high resistance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
41
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(44 citation statements)
references
References 28 publications
(52 reference statements)
3
41
0
Order By: Relevance
“…This is especially important where scientific projects and funding bodies are measuring impact to decide future funding rounds. To this end, a small circuit was created that can demonstrate the capacity for carbon nanotubes to act as electricity conductors [25]. This small demonstration (Figure 3) proves the point that carbon nanotubes are low-resistance materials, and even small power sources such as batteries are powerful enough to irradiate a small light bulb through a CNT circuit.…”
Section: Resultsmentioning
confidence: 90%
“…This is especially important where scientific projects and funding bodies are measuring impact to decide future funding rounds. To this end, a small circuit was created that can demonstrate the capacity for carbon nanotubes to act as electricity conductors [25]. This small demonstration (Figure 3) proves the point that carbon nanotubes are low-resistance materials, and even small power sources such as batteries are powerful enough to irradiate a small light bulb through a CNT circuit.…”
Section: Resultsmentioning
confidence: 90%
“…We attribute this increased resistance to a formation of a depletion region induced in the crossing area by the tubes which results in upwards band bending as the probe is brought into contact causing a more rectifying contact, this also indicates that the nanotube as semi-conducting. 13 When there is a large miss match in the two MWCNT diameters, the increase in the resistance measured at the crossing point can be up to 3 orders of magnitude higher, with resistance near the crossing point being measured in the regions of MΩ compared with kΩ away from the crossing point (i.e., Figure 2a and b). Figure 2 shows the normalized I-V plots of two crosses where the nanotubes are of similar diameter and miss-matched diameter.…”
Section: Manuscript Submitted To Nano Lettersmentioning
confidence: 99%
“…At low bias near 0.3 V, CNT-1 and CNT-2 begin to show some nonlinearity with N > 1 in Figure 5b, and an onset of transition from linear to weak nonlinear I-V behavior in Figure S4 (Supporting Information). While studying the electrical transport properties of CNTs by two-probe measurements, Barnett et al [59] observed a small nonlinearity, an onset of transition from linear to weak nonlinear I-V behavior (in the 0-1 V range) due to the presence of contamination at the interface of the probe and the CNTs. Similarly, Kawano et al [60] noticed a slight nonlinearity in an otherwise ohmic I-V curves (0-1 V range) of a single CNT.…”
Section: Resultsmentioning
confidence: 99%
“…While studying the electrical transport properties of CNTs by two‐probe measurements, Barnett et al. [ 59 ] observed a small nonlinearity, an onset of transition from linear to weak nonlinear I – V behavior (in the 0–1 V range) due to the presence of contamination at the interface of the probe and the CNTs. Similarly, Kawano et al.…”
Section: Resultsmentioning
confidence: 99%